WACANA MEDIA MASSA TENTANG KEIKUTSERTAAN UNJUK RASA KEPALA DAERAH MENOLAK KENAIKAN HARGA BBM - Karman Karman (BPSDMP Kominfo Jakarta, 2012)
Government’s initiative to r aise fuel price on April 1, 2012 was faced with demonstration in a numberof regions. In fact, local goverenment heads mobilized the people and led a demonstration. Their involvement in the demonstration made the news, evoked polemic and discourses in mass media. This writting dealt with mass media discourses regardingthat issue. This research’s used method of socialsemiotic as introduced by Halliday. That method consists of three aspects: 1) Field of discourse (what mass media’s discourse); 2) Tenor of discourse (persons on the news, their characters, positions, and roles; 3) Mode of discourse (how to describe field and tenor of discourse). This research shows that discourses on media are divided into three groups: first, discourse of law & ethics violation conducted by local government heads. Second, discourse of no-law & ethics violation. Third, discourse of no-lawviolation but ethics disrespectfullness. Discourseson media which were involved in heated fight were propalace discourse versus opponent media. Propalace discourse always referred to resources from palace’s insiders. Opponent media used politicians, critics as their resources. Those two opposing groups of media harnessed language to legitimate their own argument, and delegitimate discourse in contrasting. Rencana pemerintah menaikkan harga BBM 1 April 2012disambut aksi unjuk rasa di berbagai daerah. Kepala daerah bahkan menggerakkan massa dan memimpin jalannya unjuk rasa. Keikutsertaan mereka dalam unjuk rasa menjadi pemberitaan media massa, menimbulkan polemik dan pertarungan wacana di media massa. Tulisan ini membahas wacana media massa tentang isu di atas. Penelitian ini menggunakan metode Semiotika Sosial Halliday. Metode ini terdiri dari tiga komponen: 1) Medan Wacana (apa wacana media massa); 2) Pelibat Wacana (orang-orang yang dicantumkan dalam teks berita, sifat, kedudukan, dan peranan mereka; 3) Sarana Wacana (cara menggambarkan medan, dan pelibat wacana). Temuan penelitian menunjukkan bahwa wacana media massa terkategori menjadi 3 (tiga). Pertama, wacana adanya pelanggaran hukum dan etika yang dilakukan kepala daerah. Kedua, wacana tidakadanya pelanggaran hukum dan Etika. Ketiga, wacana tidak adanya pelanggaran hukum, namun ada pelanggaran etika. Wacana media yang sengit bertarung adalah wacana yang proistana dan media oposan. Wacana media yang proistana selalu merujuk sumberberita yang berasal dari lingkaran istana. Media oposan menjadikan politisi dan para pengamat sebagai sumber berita. Kedua kubu ini menggunakan bahasa untuk melegitimasi argumen mereka masing-masing, dan mendelegitimasi wacana yang berseberangan.